2019
DOI: 10.2196/14630
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Apps in the Clinical Care of Inflammatory Bowel Disease: Scoping Review

Abstract: Background Digital health is poised to transform health care and redefine personalized health. As Internet and mobile phone usage increases, as technology develops new ways to collect data, and as clinical guidelines change, all areas of medicine face new challenges and opportunities. Inflammatory bowel disease (IBD) is one of many chronic diseases that may benefit from these advances in digital health. This review intends to lay a foundation for clinicians and technologists to understand future di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 85 publications
(110 reference statements)
0
58
0
Order By: Relevance
“…There is a lack of randomized controlled trials investigating the educational value of such mHealth interventions; however, preliminary evidence does exist to support the use of specific educational mHealth interventions for patients with heart disease, inflammatory bowel disease and pediatric tonsillectomy, pediatric forearm fracture, and in patients with breast, colon, lung, prostate, and stomach cancers. [26][27][28][29] Anecdotally such educational platforms may hold value to patients by facilitating improvements in communication with healthcare providers and enabling a level of disease understanding that supports shared decision making in clinic. Disease-related education may also hold value for patients in remote regions to support self-management.…”
Section: Digital Therapeuticsmentioning
confidence: 99%
“…There is a lack of randomized controlled trials investigating the educational value of such mHealth interventions; however, preliminary evidence does exist to support the use of specific educational mHealth interventions for patients with heart disease, inflammatory bowel disease and pediatric tonsillectomy, pediatric forearm fracture, and in patients with breast, colon, lung, prostate, and stomach cancers. [26][27][28][29] Anecdotally such educational platforms may hold value to patients by facilitating improvements in communication with healthcare providers and enabling a level of disease understanding that supports shared decision making in clinic. Disease-related education may also hold value for patients in remote regions to support self-management.…”
Section: Digital Therapeuticsmentioning
confidence: 99%
“…Potential use cases are patient education, the management of disease monitoring, tracking of symptoms, support of medication adherence, the tracking of dietary logs and the support of patient empowerment through access to social media channels[ 39 ]. There is a large number of literature reviews that have summarized the potential of using MHAs to support patients with IBD[ 15 , 39 - 41 ]. In a recently published review from Yin et al[ 15 ], apps available in the official Google and Apple digital stores were investigated.…”
Section: Opportunitiesmentioning
confidence: 99%
“…There is a large number of literature reviews that have summarized the potential of using MHAs to support patients with IBD[ 15 , 39 - 41 ]. In a recently published review from Yin et al[ 15 ], apps available in the official Google and Apple digital stores were investigated. Eleven MHAs and 4 MAs were identified in this review.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Amnesia, incomprehension of mechanism of after effects, and impression of ineffectiveness drugs which are considered to be the most common reasons for medication non-adherence can be adequately addressed with the help of a mobile app. One of the recent studies revealed that 762 apps in the play store/app store use behavioural strategies to enhance medication adherence with the help of reminders, occasional alerts and logs (Yin et al, 2019). Interestingly many of the patients gave positive feedback on customized medication regimen details and reminders.…”
Section: Mhealth Lead Behaviour Changesmentioning
confidence: 99%